„Wirbelkörperstabilität“ im spinalen Metastasenmanagement - Wiedenhöfer, Bernd; Möhlenbruch, Markus Alfred; Hemmer, Stefan; Lehner, Burkhard; Akbar, Michael (Der Orthopäde, 2012)
BackgroundMetastases are responsible for most tumor manifestations of the spine. About 25% are symptomatic; however, due to interdisciplinary management the tumor-associated mortality is regressing. Associated acute spinal cord injury (SCI) syndromes raise patient morbidity with a loss of independence and quality of life associated with a fair potential for recovery. Therefore, the management is focused on the avoidance of SCI. The assessment of mechanical stability of vertebral bodies is a central part of decision-making when considering operative therapy. This review gives an update on the current evidence-based data for metastasis management.Decision makingThe NOMS concept is well established. Especially the parameters origin, neurologic symptoms, stability and vascularization are described and illustrated by clinical cases.Operative therapy conceptsEvidence-based operative therapy concepts are shown reflecting palliative and curative approaches.Assessment of parameters for therapy algorithmClinical and radiological parameters help to find the individual therapy. Generally a number of scores with significant time expenditure are needed. The spine instability neoplastic score (SINS) simplifies the management. Operative therapy shows the best results for the parameters pain and quality of life. However, potential perioperative and postoperative complications have to be estimated and should be avoided. Using these facts our therapy algorithm is helpful for therapy management.ConclusionsWith rising life expectancy operative therapy is of increasing relevance. Decision-making uses information about tumor origin, neurologic symptoms, stability, prognostic factors and vascularisation to determine the individual therapy.
Gesehen am 07.05.2018